Jimpitan Sebagai Pembangun Kesadaran Hukum Masyarakat Berbasis Tradisi Jawa - Fadli, Sahril (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2024)
The habit of jimpitan among the residents of neighborhood association unit 03 is expected to become a social activity that fosters a sense of mutual responsibility among residents through a collective agreement, raising the question of what motivates residents to engage in jimpitan activities and how it is implemented. This research uses the empirical research method, specifically a type of legal research that analyzes and examines the functioning of law within society and how it is implemented. The research findings indicate that jimpitan is an unwritten agreement that is quite effective in building legal awareness among the residents of neighborhood association unit 03 in Dusun Krapyak X Barepan, Margoagung Village, Sleman District, because most residents understand their roles in community life and there is a social sanction in the form of ostracism by the residents if they do not participate in jimpitan. This research shows that there are still residents who neglect this mutual agreement, because the social sanctions have not yet become a sufficiently frightening reality for the residents. Therefore, the reinforcement and implementation of social sanctions and their socialization become the homework for the neighborhood association administrators to build legal awareness among their residents.